2005
DOI: 10.1002/pssa.200461226
|View full text |Cite
|
Sign up to set email alerts
|

Pore filling of macropores prepared in p‐type silicon by copper deposition

Abstract: PACS 68.37.Hk, 81.07.Bc, 82.45.Vp Copper deposition into ordered macroporous silicon prepared in p-type substrates was investigated by immersion plating and electrochemical deposition in an aqueous solution containing Cu 2+ ions. When the sample was immersed in 0.1 M CuSO 4 solution at the open circuit potential, Cu crystallites are clearly observed at the top surface and inside the pores. The deposition of Cu oxidizes the substrate simultaneously to SiO 2 . On the other hand, the potentiostatic deposition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
1
1

Year Published

2007
2007
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 12 publications
1
33
1
1
Order By: Relevance
“…Ogata and coworkers 569,575,576 reported that shapes of deposits could be controlled as rods or tubes in ordered macroporous p-type silicon (see Figure 94). They have shown that the mechanism of the macropore filling depends on various factors, for instance, the equilibrium potential of metal, the depth of the macropore, the supporting electrolyte for electrodeposition and the displacement deposition.…”
Section: Electrochemical Processesmentioning
confidence: 97%
“…Ogata and coworkers 569,575,576 reported that shapes of deposits could be controlled as rods or tubes in ordered macroporous p-type silicon (see Figure 94). They have shown that the mechanism of the macropore filling depends on various factors, for instance, the equilibrium potential of metal, the depth of the macropore, the supporting electrolyte for electrodeposition and the displacement deposition.…”
Section: Electrochemical Processesmentioning
confidence: 97%
“…From a different point of view, there are possibilities to form various morphologies of deposits by controlling the electrodeposition reaction on the pore wall. We reported that shapes of deposits could be controlled as rods or tubes in ordered macroporous p-type silicon [13][14][15][16]. The mechanism of the macropore filling depends on various factors, for instance, the equilibrium potential of metal, the depth of the macropore, the supporting electrolyte for electrodeposition and the displacement deposition.…”
Section: Introductionmentioning
confidence: 99%
“…A limited number of studies on the filling of porous silicon with metals by electrodeposition were reported [7][8][9][10][11][12][13][14][15][16] compared with the other non-conducting template such as porous alumina and porous silica. This is because electrodeposition reactions proceed not only at the pore bottom but also on the wall, leading to the complex distribution of electric field and concentration profiles in the pore.…”
Section: Introductionmentioning
confidence: 99%
“…It is an experimental fact that the applied current density and the type of anodizing solution determine the produced pore size and morphology [2,12]. Figure 1 shows the SEM image of crosssectional (image a) and top (inset: image b) views of the porous layer produced on a heavily doped substrate under the above mentioned conditions.…”
Section: Resultsmentioning
confidence: 97%